Calcium (Ca) and Sulfur (S) for Citrus Trees - Mongi Zekri; Tom Obreza (EDIS)
Calcium and sulfur are sometimes called secondary nutrients. This term does not mean that these nutrients play a secondary role in citrus plant growth and development. Ca and S are as essential as N, P, K, Mg, and other nutrients for healthy plant growth. An inadequate supply of Ca and/or S can be a major constraint to crop production and quality. This 5-page fact sheet was written by Mongi Zekri and Tom Obreza and published by the UF Department of Soil and Water Science, July 2013.